Rape: a problem of crime classification in Islamic law - Mohd Noor, Azman (Brill Academic Publisher, 2010)
In Islam, rape is considered a serious sexual crime. Since it consists of forced sexual intercourse, most of the classical jurists called it zinā bī l-ikrāh, that is, forced unlawful sexual intercourse. The question arises whether rape is part of zinā or an isolated crime. This article focuses on the notion of rape, including a definition of this crime, its punishments, and a comparison between rape and zinā in Islamic jurisprudence.